After Delegation: The Decline of Executive Statutory Discretion in Argentina - Calvo, Ernesto; Clerici, Paula (Revista de Ciencia Política, 2020)
In this article, we introduce readers to a new concept, Executive Decoupling, which describes a statistical decline in the capacity of the Executive to modify existing legislation by decree. In contrast with Bureaucratic Delegation models, which consider legislative encroachment by the Executive as a contextual event and the result of conflict among the different branches of the government, we show that increased statutory density restrains the ability of the Executive to legislate by decree. The motive is an increase in interdependence between legislative jurisdictions, some of which connect with issues that are restricted to the President. As the citation network of existing legislation expands, increased interdependence between jurisdictions prevents the executive from innovating in contiguous normative issue areas.